METHOD OF NUMERICAL CALCULATION OF VEHICLES SPEED WITH USE OF RAPID SPLINE-TRANSFORMATION - Кужель, Н. (Science-based technologies, 2012)
The article is devoted to development of methodology,’ of car speed and acceleration estimation during the motion in a column "after a leader" on the basis of new mathematical method